Allometry and condition factor of Faunus ater (Cerithioidea: Pachychilidae) from An Estuarine Habitat of Kerala, Southern India: Allometry and condition factor of Faunus ater - Nair Rajendran, Akhil; Jisha, Sasidharan; Hari , Bharathan (Journal of Tropical Life Science, 2024)
Faunus ater is a pachychilid gastropod known to inhabit brackish water habitats of Western Indo-Pacific countries. This study aimed to analyse the morphometric relationships and condition factor of F. ater collected from the Edava-Nadayara brackish water lake of Kerala, India. Hydrographic parameters of sampling stations were recorded. A total of 1,522 specimens were collected every month from March 2019 to February 2020. The mean values recorded for total length, shell width, body whorl length, opercular length, opercular width, and total weight were 45.38±13.44 mm, 14.47±3.88 mm, 20.81±5.83 mm, 7.71±3.08 mm, 4.62±1.62 mm, and 6.97±3.72 g, respectively. The length-weight relation was obtained as Log W= -1.005+2.871 Log L. The b value (<3) indicated a negative allometric growth of the organism. Regression analysis of other morphometric measurements also showed a positive correlation (P<0.001). The analysis of Fulton’s condition factor indicated a state of well-being of F. ater in this habitat, with condition factors ranging from 5.87 to 6.99 spatially and 5.48 to 7.00 temporally. This study provides the first detailed investigation of morphometric relationships and condition factors in F. ater.